Fate and bioavailability of ¹⁴C-pyrene and ¹⁴C-lindane in sterile natural and artificial soils and the influence of aging - Smídová, Klára; Hofman, Jakub; Ite, Aniefiok E; Semple, Kirk T (Environmental pollution (1987), 2012)
Soil organic matter is used to extrapolate the toxicity and bioavailability of organic pollutants between different soils. However, it has been shown that other factors such as microbial activity are crucial. The aim of this study was to investigate if sterilization can reduce differences in the fate and bioavailability of organic pollutants between different soils. Three natural soils with increasing total organic carbon (TOC) content were collected and three artificial soils were prepared to obtain similar TOCs. Soils were sterilized and spiked with (14)C-pyrene and (14)C-lindane. Total (14)C radioactivity, HPCD extractability, and bioaccumulation in Eisenia fetida were measured over 56 days. When compared to non-sterile soils, differences between the natural and artificial soils and the influence of soil-contaminant contact time were generally reduced in the sterile soils (especially with middle TOC). The results indicate the possibility of using sterile soils as "the worst case scenario" in soil ecotoxicity studies.
Keywords: pyreny; Soil; monitorování životního prostředí; Oligochaeta; Pyrenes; Animals; Hexachlorocyclohexane; Environmental Monitoring; hexachlorcyklohexan; zvířata; látky znečišťující půdu; Soil Pollutants; půda